Tree parameters and damage characteristics on the efficacy of post extraction prophylaxis against cashew stem and root borer, Plocaederus ferrugenius - Smitha, M S; Pushpalatha, P B (Indian Journal of Plant Protection, 2020)
Two synthetic insecticides, neem oil soap and IIHR sealer cum healer were evaluated in Post Extraction Prophylaxis against cashew stem and root borer, Plocaederus ferrugineus L. during 2013-2016 at Cashew Research Station, Madakkathara, Kerala Agricultural University. Treatments were either drenched on trunk up to 1.5 meter height, exposed roots and soil near root zone using five litres or swabbed on trunk and roots with one litre insecticide solution twice a year on infested trees after extraction of insect stages and compared with control kept with removal of insect stages only. Drenching with chlorpyriphos @ 10ml/l recorded maximum recovery of 85.7 per cent trees followed with imidachloprid drenching@ 2ml/l with 80 per cent recovery. The per cent trees recovered in neem oil soap suspension swabbing @ 50ml/l was 69.5 and the respective figure in IIHR sealer cum healer was 48.5. The grub extraction (Phytosanitation) resulted in 29.2 per cent recovery. In general, there is gradual and significant reduction in recovery with increase in age, stem girth and per cent bark circumference damage and minimum recovery was observed in those trees with attack on collar, stem and root region together in all the treatments. The recovery after PEP significantly reduced with increase in age, girth, per cent bark circumference damage and yellowing and was significantly less in trees with attack on collar, root and stem together in trees under phytosanitation treatment. However, in sealer cum healer, the recovery was significantly varied with respect to per cent bark circumference damage and zone of attack. On cost worthiness, chlorpyriphos (Rs. 89 /tree/ year), imidachloprid (Rs. 82 /tree/year) and neem oil soap (Rs.75/tree/year) were quite feasible.